Optimization of Prunus napaulensis fruit yoghurt process parameters using Response Surface Methodology with enhanced nutritional and sensory attributes - Kashung, Phareichon; Devi, Karuthapandian; Groover, Chand Ram (Indian Journal of Dairy Science, 2025)
This study aimed to optimize the process parameters for developing yoghurt enriched with Prunus napaulensis, a nutrient-rich indigenous fruit, using Response Surface Methodology (RSM) to enhance its nutritional and sensory attributes. The yoghurt was formulated with varying levels of fruit pulp (6-8%), inoculum (1-2%), incubation time (4-8 hours), and incubation temperature (37- 42°C). The optimization targeted pH and titratable acidity as key responses. A Central Composite Rotatable Design (CCRD) was employed, and the statistical analysis revealed significant models with R2 values of 0.9493 and 0.9663 for pH and titratable acidity respectively. The formulation -7% fruit pulp, 1.5% inoculum, incubation at 39°C for 6 hours- yielded a product with desirable pH and acidity. Sensory evaluation indicated that the fruit yoghurt exhibited improved colour and texture due to natural pigments and fibre content, though overall acceptability remained comparable to traditional yoghurt. Physicochemical analysis confirmed enhanced nutritional value, notably increased protein, carbohydrates, vitamins, minerals and anthocyanin content, making it a superior alternative to standard yoghurt. However, the fruit yoghurt demonstrated lower water holding capacity and higher syneresis, impacting texture. Microbial analysis confirmed product stability and safety throughout a 21- day storage period. In conclusion, Prunus napaulensis offers significant potential for developing value-added dairy products, providing year-round availability of the fruit. The study supports its commercial viability and underscores its role in diversifying yoghurt products while aligning with consumer preferences for health-conscious foods. Further investigations should explore the long-term health benefits and market acceptance of the developed fruit yoghurt.